2022
DOI: 10.1111/roiw.12599
|View full text |Cite
|
Sign up to set email alerts
|

Economic insecurity, racial anxiety, and right‐wing populism

Abstract: This paper studies the roles of economic insecurity (EI) and attitudes to racial inequality as predictors of voting patterns in the 2016 US election. Using data from the 2016 Voter Survey, we show that both perceptions of EI and concerns over anti-White discrimination are significant correlates of Republican support. Effect sizes on racial attitudes are much larger than those found on EI, although the effects of insecurity become larger when accounting for both short-term and long-term economic stress. We also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…However, these are still indirect proxies of the expectation of a status decline. The study that comes closest to measuring subjective perceptions of both experiences and expectations of status decline was conducted by Rebechi and Rohde (2022). As their research focuses on the electoral impact of economic insecurity, the authors used two variables based on respondents’ assessment of how their financial situation had changed from the past and how their lives might change in the future.…”
Section: Experience Of Status Decline and Expectation Of Status Declinementioning
confidence: 99%
See 1 more Smart Citation
“…However, these are still indirect proxies of the expectation of a status decline. The study that comes closest to measuring subjective perceptions of both experiences and expectations of status decline was conducted by Rebechi and Rohde (2022). As their research focuses on the electoral impact of economic insecurity, the authors used two variables based on respondents’ assessment of how their financial situation had changed from the past and how their lives might change in the future.…”
Section: Experience Of Status Decline and Expectation Of Status Declinementioning
confidence: 99%
“…Yet, few studies compare the experience of status decline against the expectation of status decline within this burgeoning scholarship (for an exception, see Engler and Weisstanner, 2020;Rebechi and Rohde, 2022). One of the main reasons for the lack of this comparison is the paucity of direct measures of both types of status decline which, in turn, increases a reliance on imperfect proxies.…”
Section: Experience Of Status Decline and Expectation Of Status Declinementioning
confidence: 99%
“…Certainly, the radical right parties are characterized by male politicians and voters, and their programs defend family values and oppose pro‐women measures on the grounds that equality has been achieved (Dancygier 2020). In this vein, Rebechi and Rhode's (2023) study of voting for Donald Trump found that the cultural explanator of “perceived reverse discrimination” was quantitatively more important than employment insecurity, often by a factor of two or three (see also Baccini and Weymouth 2021). Similarly, studies in Sweden (Off 2023) and Spain (Anduiza and Rico 2023) suggest that periods of strong feminist mobilization produced a backlash that boosted the radical right in subsequent elections.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Inside majoritarian countries, there have been ruptures inside traditional conservative parties that have led them to an increasingly populist tactic (Norris and Inglehart 2019). Hostility to immigration stemming from fears of its disruption to local labor markets is a central theme in the scholarly and public literature explaining a turn to far‐right candidates and political parties (Baccini and Weymouth 2021; Ferrari 2021; Rebechi and Rohde 2023). A central part of the argument is that in the wake of the widespread shift to more flexible labor markets, workers experience greater fear for their jobs and livelihoods.…”
mentioning
confidence: 99%
“…Second, a number of recent works have documented that economic anxiety can affect economic and political decision making. They show that economic insecurity is robustly associated with populist and right‐wing party support (see e.g., Algan et al 2017; Guiso et al 2017; Guiso et al 2019; Bossert et al 2022; Dippel et al 2021; Rebechi and Rohde 2022; Watson et al 2022) as well as with Brexit choice (Colantone and Stanig 2018; Liberini et al 2019). There is also considerable evidence that indicates that households with insecure property rights systematically invest less, and this has been observed in settings as diverse as rural China (Jacoby et al 2002), India (A. V. Banerjee et al 2002), Ghana (Goldstein and Udry 2008) and Argentina (Galiani and Schargrodsky 2010).…”
Section: Introductionmentioning
confidence: 99%